Frequency‐Dependent Dual‐Functional Coding Metasurfaces at Terahertz Frequencies. Issue 12 (4th September 2016) - Liu, Shuo; Zhang, Lei; Yang, Quan Long; Xu, Quan; Yang, Yan; Noor, Ahsan; Zhang, Qian; Iqbal, Shahid; Wan, Xiang; Tian, Zhen; Tang, Wen Xuan; Cheng, Qiang; et al.
Abstract : A frequency‐dependent dual‐functional coding metasurface is proposed at terahertz frequencies using two layers of metamaterial structures, each of which is responsible for the independent control of reflection phases at two distinct frequencies. The zero interference between the functionalities at the lower and higher frequencies are promising for possible applications in multicolor holography for color displays or a frequency beam splitter.